Research Progress and Prospects of Phosphorus-Based New Energy Battery Materials - Lich, Elizabeth; Osgood, Gathaniel G. (Journal of Green Energy and Environmental Engineering, 2026)
Amid escalating worldwide energy requirements and intensifying environmental imperatives, the advancement of novel energy materials has surfaced as a central research priority. The phosphorus chemical sector, constituting an integral component of the emerging energy landscape, fulfills a critical function in catalyzing green energy industry proliferation. This discourse examines the deployment of phosphate-derived materials within next-generation battery technologies, encompassing cathode compositions such as lithium iron phosphate and lithium manganese iron phosphate for lithium-ion systems, alongside sodium vanadium phosphate with NASICON framework architecture for sodium-ion battery negative electrodes. The research progress in liquid lithium salt electrolyte LiPF₆, solid electrolyte superionic conductor lithium aluminum titanium-phosphate and anode electrode materials such as phosphorus and phosphorus compounds were discussed. The characteristics of these materials and the possible challenges in the process of implementation were presented, such as the poor electrochemical stability of phosphorous cathode materials due to low electrical conductivity, which could be improved by material modification and nano-chemical synthesis technology. The research and application of phosphate-based new energy materials would continue to promote the growth of green energy industry and provide new ideas and solutions to solve energy and environmental problems.